Comment
Share
Q)

# The equation of projection of the line $\large\frac{x-1}{2}=\frac{y-2}{1}=\frac{z-3}{3}$ on the plane $x+y+z=1$ is given by ?

$\begin{array}{cc}(a)\:x+y+z-1=0=2x-y-z+3\: & (b)\:x+y+z-1=0=x-2y-z+3\: \\ (c)\:x+y+z-1=0=x-y-2z+3\: & (d)\:x+y+z-1=0=2x-y-z-3\end {array}$

Comment
A)
Toolbox:
• Projection of a line on a plane is the line of intersection of the given plane and the plane $\perp$ to this plane which contains the given line.
Given line is $\large\frac{x-1}{2}=\frac{y-2}{1}=\frac{z-3}{3}............(i)$
Given plane is $x+y+z-1=0.................(ii)$
$d.r.$ of the normal $(\overrightarrow n)$ to the plane containing (i) is $\perp$ to
normal to the plane $(ii)= (1,1,1)$ and also is $\perp$ to the line $(i)=(2,1,3)$
$\therefore \overrightarrow n=(1,1,1)\times(2,1,3)=(2,-1,-1)$
Vector $\perp$ to $\overrightarrow a\:\:and\:\:\overrightarrow b$ is $\overrightarrow a\times\overrightarrow b$
$\therefore$ The eqn. of the plane containing $(i)$ and $\perp$ to $(ii)$ is given by
$2x-y-z+d=0.......(iii)$
But since every point on the line $(i)$ satisfies the eqn. of the plane containing it, $(1,2,3)$
satisfies the equation.
$\Rightarrow\:2-2-3+d=0$ $\Rightarrow\:d=3$
$\therefore$ the eqn. of the plane (iii) becomes $2x-y-z+3=0$
As per the definition of projection of the line $(i)$ on the plane $(ii)$ is given by $(ii)$ and $(iii)$
$i.e.,\:\:x+y+z-1=0=2x-y-z+3$